People in intensive care with COVID‐19: demographic and clinical features during the first, second, and third pandemic waves in Australia. (9th June 2022) - Begum, Husna; Neto, Ary S; Alliegro, Patricia; Broadley, Tessa; Trapani, Tony; Campbell, Lewis T; Cheng, Allen C; Cheung, Winston; Cooper, D James; Erickson, Simon J; French, Craig J; Litton, Edward; et al.
Abstract: Objective: To compare the demographic and clinical features, management, and outcomes for patients admitted with COVID‐19 to intensive care units (ICUs) during the first, second, and third waves of the pandemic in Australia. Design, setting, and participants: People aged 16 years or more admitted with polymerase chain reaction‐confirmed COVID‐19 to the 78 Australian ICUs participating in the Short Period Incidence Study of Severe Acute Respiratory Infection (SPRINT‐SARI) Australia project during the first (27 February – 30 June 2020), second (1 July 2020 – 25 June 2021), and third COVID‐19 waves (26 June – 1 November 2021). Main outcome measures: Primary outcome: in‐hospital mortality. Secondary outcomes: ICU mortality; ICU and hospital lengths of stay; supportive and disease‐specific therapies. Results: 2493 people (1535 men, 62%) were admitted to 59 ICUs: 214 during the first (9%), 296 during the second (12%), and 1983 during the third wave (80%). The median age was 64 (IQR, 54–72) years during the first wave, 58 (IQR, 49–68) years during the second, and 54 (IQR, 41–65) years during the third. The proportion without co‐existing illnesses was largest during the third wave (41%; first wave, 32%; second wave, 29%). The proportion of ICU beds occupied by patients with COVID‐19 was 2.8% (95% CI, 2.7–2.9%) during the first, 4.6% (95% CI, 4.3–5.1%) during the second, and 19.1% (95% CI, 17.9–20.2%) during the third wave. Non‐invasive (42% v 15%) and prone ventilation strategies (63% v 15%) were used more frequently during the third wave than during the first two waves. Thirty patients (14%) died in hospital during the first wave, 35 (12%) during the second, and 281 (17%) during the third. After adjusting for age, illness severity, and other covariates, the risk of in‐hospital mortality was similar for the first and second waves, but 9.60 (95% CI, 3.52–16.7) percentage points higher during the third than the first wave. Conclusion: The demographic characteristics of patients in intensive care with COVID‐19 and the treatments they received during the third pandemic wave differed from those of the first two waves. Adjusted in‐hospital mortality was highest during the third wave.